The effect of fermented dairy intake and abdominal obesity in adults: a systematic review and dose–response meta-analysis of cohort studies - Fatemeh Sadat Hashemi Javaheri; Milad Nasiri Jounaghani; Amirhossein Sahebkar; Mostafa Norouzzadeh; Pedram Delgarm; Hossein Shahinfar; Artemiss Mirdar Harijani (Eating and Weight Disorders)
Abstract Objectives Diverse analysis has analyzed the potential efficacy of consuming foods created through the fermentation of dairy in mitigating abdominal obesity. The current meta-analysis aims to determine the impacts of consuming fermented dairy foods and the occurrence of abdominal obesity. Methods Web of Science, PubMed, and Scopus databases were queried for records published before January 13, 2023, to investigate proportionate cohort studies. We employed a random-effects model to appraise the relative risk (RR); effect size was assessed through the 95% confidence interval (CI). Additionally, a one-stage dose–response analysis was executed, quality assessment was conducted through the ROBINS-E tool. Results Consequently, five publications, comprising 41,430 cases, were included as selected studies. The pooled effect shows an effect on the abdominal obesity risk; however, the effect was not significant. Subgroup analyses revealed a potential risk reduction effect in high- and low-fat and fermented dairy productions, although the findings were not statistically significant. Furthermore, the dose–response analysis indicated a linear decrease in risk with increasing consumption of high-fat fermented yogurt, with an HR of 0.84 (95% CI 0.71, 0.99) by 8 servings/week and an HR of 0.37 (95% CI 0.19, 0.71) by 21 servings/week. Conclusion These findings imply the potential effectiveness of fermented dairy products, particularly high-fat yogurt, in diminishing the obesity risk. However, further research addressing the limitations of previous studies is essential to confirm these results. Evidence-based medicine level: No level of evidence: Level of evidence III. PROSPERO registration number: CRD42023387538 ( http://www.crd.york.ac.uk/PROSPERO ).